Growth models from a brassinosteroid perspective. (February 2020) - Ackerman-Lavert, Michal; Savaldi-Goldstein, Sigal
Highlights: Core BR signaling components involve BR ligand-dependent and ligand-independent regulation. Spatiotemporal BR activity controls both longitudinal and radial root growth. BR and auxin occurrence is both similar and opposing. Microtubule organization and cell wall composition are modulated by BR. Abstract : Plant growth relies on interconnected hormonal pathways, their corresponding transcriptional networks and mechanical signals. This work reviews recent brassinosteroid (BR) studies and integrates them with current growth models derived from research in roots. The relevance of spatiotemporal BR signaling in the longitudinal and radial root axes and its multifaceted interaction with auxin, the impact of BR on final cell size determination and its interplay with microtubules and the cell wall are discussed. Also highlighted are emerging variations of canonical BR signaling that could function in developmental-specific context.